Asuhan Keperawatan Pada An. H Dengan Gastroenteritis Akut (Gea) Di Ruang Anyelir Rsud Waled Kabupaten Cirebon - Dewi Oktoviani; Erida Fadila; Evi Nurmala Fia; Kiki Ameliya; Rizal Nova Jalaludin (Awatara Publisher, 2024)
Acute gastroenteritis (GEA) is one of the most common diseases in children around the world, including Indonesia. The impact of GEA if not treated immediately can cause dehydration. This study aims to apply nursing care to An. H with hypovolemia nursing problems using the nursing process, namely: assessment, nursing diagnosis, intervention, implementation, and evaluation. This type of research is descriptive with a case study form. Data collection was carried out by interview, observation, physical examination, supporting examination, and documentation with focal data of liquid stools ˃5x a day and vomiting ≥3x a day. The interventions applied are hypovolemia management and fluid monitoring with the main nursing actions of fluid rehydration. After taking nursing actions on An. H with acute gastroenteritis in treatment for 3x24 hours shows that the diagnosis/nursing problem of hypovolemia associated with active fluid loss can be resolved. It can be concluded that nursing care by providing rehydration is the first aid to prevent dehydration and restore lost body fluids during diarrhea